Efficacy of GP-11 KHV DNA Vaccine in Common Carp (Cyprinus carpio) through Feed by Different Frequency of Administration - Ahmad Beni Rouf; Sri Nuryati; Sukenda Sukenda; Alimuddin Alimuddin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
GP-11 KHV DNA vaccine is a vaccine that can be used to induce immunity against the KHV virus (Koi herpesvirus). Vaccination through feed is an alternative way of administering vaccines. The study aimed to examine the effect of giving KHV GP-11 DNA vaccine through feed with different frequencies to KHV infection. The frequency of vaccine administration is GP-11 vaccination once a week; GP-11(1x), GP-11 vaccination twice a week; GP-11(2x), GP-11 vaccination three times a week; GP-11(3x), GP-25 vaccinations three times a week; GP-25(3x), negative control (without KHV test) and positive control (KHV tested). The fish were kept for 28 days after vaccination and then continued with the KHV challenge test for 28 days. The weight of carp ranges from 13.82±2.37 g maintained with a density of 15 fish/aquarium. The results showed that vaccine treatment was able to induce an immune response as indicated by the number of white blood cells, lysozyme activity and post-vaccination antibody titer showed a significant effect compared to controls. Likewise, after the challenge test, supported by IFNγ and IgM gene expression parameters after the challenge test showed the highest value of vaccine treatment rather than control. The efficacy of vaccine was showed by RPS value (%) in each vaccine treatment obtained GP-11(1x) value of 44.7±3.7a, GP-11(2x) of 78.9±18.2b, GP-11(3x) 85.6±12.6b and GP-25(3x) 79.5±18.1b. It was concluded that administering the GP-11 vaccine frequency 2 times a week provides protection as strong as giving a vaccine frequency 3 times a week.Keywords: common carp, DNA vaccine, frequency of administration, koi herpesvirus